Integrating resource oriented sanitation technologies with urban agriculture in developing countries: measuring the governance capacity of Arba Minch City, Ethiopia - Ejigu, Abrham Kassa; Yeshitela, Kumelachew (Frontiers in Sustainable Cities, 2023)
This research study aims to assess the capacity of Arba Minch City to adopt resource-oriented sanitation technology and integrate it with urban agriculture. The overarching goal is to promote sustainable urban development by not only using resources efficiently but also recovering resources from urban waste streams. To measure the city's governance capacity, the study employs a Governance Capability Framework (GCF), which identifies nine conditions and three indicators for each condition across three dimensions: knowing, wanting, and enabling. The framework helps assess the city's capacity for governance throughout the integration of urban agriculture with ecological sanitation (ecosan) technology. The research employs a triangle strategy, which consists of desk research, gray and scientific literature review, and a semi-structured interview with 27 indicators. By employing these strategies, the research evaluates Arba Minch's governance capacity to implement ecological sanitation integration with urban agriculture. The findings of the study show that Arba Minch City's governance capacity to integrate ecosan with urban farming is affected by several factors. These factors include a lack of systematic monitoring and evaluation of previous projects, fragmentation of policy tools to govern the integration of the system, and a lack of adequate public sector participation. Additionally, there is no government body responsible for integrating the system, and various non-governmental organizations play a significant role in financing, organizing, and implementing the system. On the user side, the study reveals a behavioral gap in adapting to resource-oriented sanitation technology and recovered organic fertilizer. The findings suggest that long-term system management requires a strong, active, and well-trained community group capable of taking on the role and responsibility of running similar projects. Furthermore, to mitigate the policy fragmentation challenge, policy harmonization and integration among actors to negotiate, deliberate, and agree on measures to be taken are critical. In conclusion, the study suggests that similar project developers should investigate the factors that motivate users of new technology and influence their behavioral changes. Ultimately, the study recommends a more comprehensive approach to resource-oriented sanitation technology and urban agriculture integration that takes into account governance capacity and community engagement.